Peran Petugas Puskesmas dalam Promosi Kesehatan Berhenti Merokok pada Pasien dan Masyarakat - Muhammad Daroji, Yayi Suryo Prabandari, Ira Paramastri (Berita Kedokteran Masyarakat (BKM), 2011)
Role of Health Center Staff in Health Promotion of Smoking Cessation of Patients and The CommunityBackgrounds: Smoking is a complex and global problem. Its impact to health is undeniable. Nevertheless, the prevalence of smoking increases in developing countries, whereas in developed countries the prevalence decreases. The prevalence of smoking in population always increases. In the Sleman district the prevalence of smoking in the population of above 10 years old reaches 26.7%, the prevalence of smoking household is 55.74%. Data of 8 major diseases causing mortality in hospitals at District of Sleman shows that 4 of them are diseases related to cigarettes. Health staffshave a very strategic role to promote smoking cessation in patientsand the community.Objectives:  To identify the role of health center staff promoting healthty smoking cessation in patients and community and aspects related to it.Methods: The study used qualitative approach and phenomenological design. The main subject of the studywas staff of public health promotion, clinical coordinator and heads of health center. The supporting subjects were patients and the community and the officials of the health office. Selection of health centers were based on coverage of the highest and the lowest smoke free household, each representing one respondent. Data were obtained through indepth interview and observation.Results: Role of health center staff in the promotion of smoking cessation includes patient and family education,community and school children education, giving advices and medical instructions, providing information, becoming non smoking role model, creating a model of smoke free area, collaborating clinical services with psychologists. Aspects related to these comprised were staff’s attitudes, understanding of the need to quit smoking, responsibility, staff’s competence, community’s expectation, constraints and belief in success.Conclusions: Role of health center staff in the promotion of smoking cessation was not yet optimum due to limited competence, internal and external constraints, poor belief in success.Keywords: role of staff, health promotion, smoking cessation